Functional Outcome of Flexible Intramedullary Nailing in Children with Femoral Shaft Fractures - Muhammad Ziad, Ali Ammad, Rehman Azmat, Adeel Hameed, Syed Imran Haider, Zahid Hafeez (Pakistan Journal of Medical & Health Sciences, 2024)
Femoral shaft fractures are the second most common long-bone fractures in children. An ideal treatment should ensure proper alignment, patient comfort, and family convenience. This study aims to investigate the functional outcomes of using flexible titanium intramedullary nails for pediatric femoral shaft fractures, addressing the limited local evidence for their effectiveness. OBJECTIVE: To determine the functional outcome of flexible intramedullary nailing in children with femoral shaft fractures STUDY SETTING: The study was conducted at Orthopedics Surgery Unit-II, Jinnah Hospital, Lahore. DURATION OF STUDY: September 16, 2022, to March 16, 2023 STUDY DESIGN: Descriptive case series SUBJECTS & METHODS: A total of 60 patients with femoral shaft fractures were enrolled in the study. Brief history-taking, physical and radiological examinations, and investigations were performed. Retrograde intramedullary nailing was done with two nails of the same diameter under an image intensifier. Follow-up of the patients was performed at 3-weekly intervals until radiological union occurred. Functional assessment was done. Data were entered and analysed in SPSS v25.0. Gender-, BMI-, and age-stratified data to account for effect modifiers. A p-value ≤0.05 was considered statistically significant after applying the Chi-square test. RESULTS: A total of 60 patients with femoral shaft fractures were included in this study. There were 46(76.7%) male and 14(23.3%) female. The mean age of the patients was 7.18±2.259 years. Of 58 patients, 58 (96.7%) had satisfactory functional outcome. CONCLUSION: Intramedullary elastic nailing of simple shaft of femur fractures in children is an effective method with negligible complications. Treatment cost can be significantly lowered by using the much cheaper stainless steel flexible nails rather than the more expensive titanium nails. KEY WORDS: Femoral Shaft Fractures, Intramedullary Nailing, Flynn’s Criteria.